2018
DOI: 10.1021/acsphotonics.8b00525
|View full text |Cite
|
Sign up to set email alerts
|

100 GHz Plasmonic Photodetector

Abstract: Photodetectors compatible with CMOS technology have shown great potential in implementing active silicon photonics circuits, yet current technologies are facing fundamental bandwidth limitations. Here, we propose and experimentally demonstrate for the first time a plasmonic photodetector achieving simultaneously record-high bandwidth beyond 100 GHz, an internal quantum efficiency of 36% and low footprint. High-speed data reception at 72 Gbit/s is demonstrated. Such superior performance is attributed to the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 43 publications
3
145
0
1
Order By: Relevance
“…Combining these results, a 50 GHz bandwidth has been obtained at a reverse bias voltage of 2 V for a Ge width of 0.3 μm and at 3 V for a Ge width of 0.5 μm [22]. To enhance the electric field in the Ge, the metal-semiconductor-metal (MIM) plasmonic waveguide has been proposed where the electric field is highly enhanced in the slot between the two metals [24]. Compared with other SPP waveguide arrangements, the MIM fundamental mode does not exhibit a cut-off, even for very small thicknesses of semiconductor layer.…”
Section: Germanium Photodetectorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Combining these results, a 50 GHz bandwidth has been obtained at a reverse bias voltage of 2 V for a Ge width of 0.3 μm and at 3 V for a Ge width of 0.5 μm [22]. To enhance the electric field in the Ge, the metal-semiconductor-metal (MIM) plasmonic waveguide has been proposed where the electric field is highly enhanced in the slot between the two metals [24]. Compared with other SPP waveguide arrangements, the MIM fundamental mode does not exhibit a cut-off, even for very small thicknesses of semiconductor layer.…”
Section: Germanium Photodetectorsmentioning
confidence: 91%
“…However, to achieve even such results, a very large voltage exceeding 10 V is required. As the MIM field is confined in a narrow Ge region, 100-200 nm, short drift paths for photogenerated carriers are achieved, producing a high speed photoresponse exceeding 100 GHz [24].…”
Section: Germanium Photodetectorsmentioning
confidence: 99%
“…a) 3D amorphous germanium‐based first high‐speed plasmonic photodetector. Adapted with permission . Copyright 2018, American Chemical Society.…”
Section: Mechanism Of Plasmonic‐assisted Devicesmentioning
confidence: 99%
“…Salamin et al reported the 3D amorphous germaniumbased first high-speed plasmonic photodetector as shown in Figure 21a. [126] They observed the phenomena in which the premier speed was conceivable due to the variation of the wavelength of optical energy in the photodetection-based plasmonic-germanium waveguide detector. An amalgamation of plasmonic-based design with engrossing semiconductors allows the effective and uppermost-speed photodetection.…”
Section: Light Sensing (Photodetectors) Devicesmentioning
confidence: 99%
See 1 more Smart Citation